THE VALUE OF LABORATORY WORK IN THE NATURAL SCIENCES FOR STUDENTS IN PROGRAMS OF GENERAL EDUCATION. - Postl, Anton (Science Education, 1965)
The article presents a study that examines the importance of laboratory work in the natural sciences for talented students enrolled in programs of General Education, at the Oregon State College in Oregon. The research has also determined the no significant differences between the laboratory and lecture groups. The peculiar methods of solving problems, observing and drawing concordant conclusions were considered in order to importance of laboratory activities in natural sciences. It concluded that individual laboratory work provides a greater opportunity for expression of individual differences.